What Motivates Rice Farmers to Adopt Hybrid Rice Technology in Assam, India? - Jeemoni Gogoi; Rinumoni Buragohain, Nivedita Deka (Indian Journal of Extension Education, 2022)
To feed the rising population there is need for improved technologies like hybrid rice cultivation which gives comparatively higher yield than other rice varieties. A study was conducted to find the factors affecting the adoption of hybrid rice in Nagaon district of Assam using logistic regression analysis in the year 2018. The results revealed that, adoption of hybrid rice was positively and significantly affected by socio-economic factors such as occupation, number of extension agent contact, while the age of the farmers and farm size were found to affect the rate of adoption negatively indicating that rate of adoption of hybrid rice was higher with main occupation as agriculture and more extension agent contact of the farmer whereas older famers and large farmers were reluctant to grow hybrid rice. The major problem faced by the hybrid rice adopters was rain during harvesting time and by the non-adopters was poor cooking quality of hybrid rice. For increasing the adoption of hybrid rice varieties, government need to consider the problems faced by the farmers in its adoption and provide community threshing floor, timely supply of seed in sufficient quantity and awareness on new technology to the farmers through the extension personnel.